Isolation and Characterization of Single-Chain Protein S - Meijer-Huizinga, Fenny; Mertens, Koen; van Mourik, Jan A (Thrombosis and Haemostasis, 1994)
Protein S is a vitamin K-dependent cofactor of activated protein C in the proteolytic cleavage and concomitant inactivation of the coagulation factors Va and Villa. Protein S is sensitive to proteolysis by thrombin which reduces its functional activity. Uncontrolled proteolytic breakdown, leading to the generation of a two-chain molecule, is commonly encountered during the purification of both human and bovine protein S. In this study we demonstrate that human, single-chain, intact protein S can be isolated from plasma in a single step by affinity chromatography using a monoclonal antibody, CLB PS 52, directed to an epitope located within the thrombin-sensitive region of protein S. The product of purification was readily cleaved by thrombin after Arg49, resulting in a two-chain molecule which demonstrated a lower reactivity towards CLB-PS 52 than the parent single-chain protein. This study for the first time shows that intact protein S can be isolated directly from plasma using a monoclonal antibody selected for its ability to recognize uncleaved protein S.